Satellite formation flying : relative dynamics, formation design, fuel optimal maneuvers and formation maintenance /: relative dynamics, formation design, fuel optimal maneuvers and formation maintenance. (2016) - Wang, Danwei; Poh, Eng Kee; Wu, Baolin
No abstract available